Maternal serum albumin in the late trimester and birth weight: a cross-sectional study from Jiangxi, China - Jun Xiong; Huan Li; Jian-Min Zhang; Shi-Qi Li; Chang Ge; Hui-Xin Zheng; Xiao-Qing Tan; Jia-Wei Zheng; Xiao-Ju He; Shu-Ying Zhu (PLoS ONE, 2025)
Background The links of maternal serum albumin (ALB) concentration in the late trimester and infant birth weight remain equivocal. Accordingly, we focused on the investigation of the correlation of maternal serum albumin concentration and infant birth weight among women during pregnancy in Jiangxi, China. Methods 1214 subjects were recruited for the present cross-sectional study. Infants of low birth weight (LBW) had a weight <2500g when they are born. Albumin was categorized as <30, 30-<35 and ≥35 g/L, with a concentration of <30g/L indicating hypoproteinemia. Low birth weight and the correlations of maternal serum albumin concentration in the late trimester and infant birth weight were evaluated binary logistic regression analyses and linear regression on the basis of multiple variables, separately. Results The overall prevalence of hypoproteinemia was 7.83%. Maternal serum albumin concentration in the late trimester was positively correlated to infant birth weight (β, 0.03; 95% confidence interval [CI]: 0.02, 0.04), as indicated by multivariate linear regression analyses. Besides, a negative correlation of maternal serum albumin concentration in the late trimester and low birth weight (odds ratio [OR], 0.84; 95 percent CI: 0.78, 0.91) was reported through multivariable binary logistic regression analyses, which showed consistency with the above result. In comparison to individuals in ALB < 30 g/L group of maternal serum albumin, the adjusted β and OR values of albumin for infant birth weight and low birth weight were 0.40 (95 percent CI: 0.26, 0.54) and 0.18 (95 percent CI: 0.09, 0.39), separately. Results of smoothing curve fitting confirmed the linear correlation of maternal serum albumin and infant birth weight and low birth weight. Maternal serum albumin and infant birth weight were consistent in the subgroups below: smoking habit, antenatal visits, sex of the newborn, education, maternal age, parity, hemoglobin, pre pregnancy body mass index (BMI) and gestation age at delivery. Conclusion A higher maternal serum albumin in the late trimester is associated with a lower risk of infant birth weight. The data suggests that maternal serum albumin in the late trimester may serve as a simple and effective tool for the assessment of the low birth weight risk in clinical practice.